Catalytic Membrane Aided Pervaporation Applications in Esterification Reactions - Ünlü, Derya (Bilecik Şeyh Edebali Üniversitesi, 2020)
The development of the chemical industry has resulted in the usage more solvents in various chemical and physical processes. The increase in the amount of used solvent also increases the economic burden to the industry. The recovery, reuse, and purification of solvents became the essential requirements of the industry. In addition, the obtainment of high-quality, economic product with low environmental impact and high yield is important. The catalytic membrane aided pervaporation application is considered as one of the new alternative solutions of both reaction and separation problems in the industries. Catalytic membrane aided pervaporation application is one of the developing membrane technologies. It is a hybrid and integrated process combining separation and reaction units. This article is concentrated on catalytic membrane aided pervaporation applications of the esterification reactions. Some important information about catalytic membrane, pervaporation and catalytic membrane aided pervaporation has been firstly reported. Different configurations of catalytic membrane aided pervaporation have been defined and explained. Advantages of the hybrid catalytic membrane aided pervaporation processes have been listed. The factors affecting the catalytic membrane aided pervaporation are briefly discussed. The important catalytic membrane aided pervaporation, reaction conditions and the obtained results in literature are also summarized. The important catalytic membrane aided pervaporation studies in literature, operation conditions and the obtained results have been summarized.

Kimya endüstrisinin gelişmesi, çeşitli kimyasal ve fiziksel işlemlerde daha fazla çözücü kullanılmasına neden olmuştur. Kullanılan solvent miktarının artması da sektöre olan ekonomik yükü arttırmaktadır. Çözücülerin geri kazanılması, yeniden kullanılması ve saflaştırılması endüstrinin temel gereksinimleri haline gelmiştir. Ayrıca yüksek kaliteli, düşük çevresel etkili, verimi yüksek, ekonomik ürün elde edilmesi önemlidir. Katalitik membran destekli pervaporasyon uygulaması, endüstrilerdeki hem reaksiyon hem de ayırma problemlerine yeni alternatif çözümlerinden biri olarak kabul edilmektedir. Katalitik membran destekli pervaporasyon uygulaması gelişen membran teknolojilerinden biridir. Ayırma ve reaksiyon birimlerini birleştiren hibrit ve entegre bir süreçtir. Bu çalışma, esterleştirme reaksiyonlarının katalitik membran destekli pervaporasyon uygulamaları üzerine yoğunlaşmıştır. İlk olarak, katalitik membran, pervaporasyon ve katalitik membran destekli pervaporasyon hakkında bazı önemli bilgiler verilmiştir. Katalitik membran destekli pervaporasyonun farklı konfigürasyonları tanımlanmış ve açıklanmıştır. Hibrit katalitik membran destekli pervaporasyon işlemlerinin avantajları listelenmiştir. Katalitik membran destekli pervaporasyonu etkileyen faktörler kısaca tartışılmıştır. Literatürdeki önemli katalitik membran destekli pervaporasyon çalışmaları, çalışma koşulları ve elde edilen sonuçlar özetlenmiştir.
Esterleşme Reaksiyonlarında Katalitik Membran Destekli Pervaporasyon Uygulamaları
Keywords: Engineering; Mühendislik